2004
DOI: 10.1111/j.1399-3054.2004.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

How do salinity and water stress affect transport of water, assimilates and ions to tomato fruits?

Abstract: The study was conducted in order to determine whether water stress affects the accumulation of dry matter in tomato fruits similarly to salinity, and whether the increase in fruit dry matter content is solely a result of the decrease in water content. Although the rate of water transport to tomato fruits decreased throughout the entire season in saline water irrigated plants, accumulation rates of dry matter increased significantly. Phloem water transport contributed 80–85% of the total water transport in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 32 publications
(66 reference statements)
5
39
1
1
Order By: Relevance
“…Sucrose concentration of the phloem sap ranged from 3 to 7% in 'House Momotaro' and 1 to 10% in 'Saturn', depending on the treatments. These values are approximately equivalent to the estimation by Ho et al (1987) and Plaut et al (2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sucrose concentration of the phloem sap ranged from 3 to 7% in 'House Momotaro' and 1 to 10% in 'Saturn', depending on the treatments. These values are approximately equivalent to the estimation by Ho et al (1987) and Plaut et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are no reports which describe the successful collection and quantification of phloem sap that enters tomato fruits. The only method available is based on the estimation of the rate of water import through the phloem and that of carbohydrates (Ho et al, 1987;Plaut et al, 2004). Water import through the phloem could be estimated by the reduction in fruit growth after heat-girdling (Plaut et al, 2004); however, these reports discuss changes in the phloem sugar as a result of saline stress and do not focus on the relationship of phloem sugar and fruit solids.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Tomato fruit growth results from the influx of water, carbon and minerals through the xylem and the phloem, which is driven by a gradient in hydrostatic and osmotic potential between the stem and the fruit. It is generally acknowledged that the phloem accounts for 80-90% of the influx, whereas the xylem only has a minor contribution (Ehret and Ho, 1986;Ho et al, 1987;Plaut et al, 2004;Guichard et al, 2005). Recently, Windt et al (2009) used magnetic resonance imaging (MRI) to study water flow into developing tomato fruits and demonstrated that xylem influx accounted for at least 75% of the net influx.…”
Section: Introductionmentioning
confidence: 99%